2022
DOI: 10.3390/ijerph19127348
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis of Femoral Head—Overview and Current State of the Art

Abstract: Avascular necrosis (AVN) of the femoral head is caused by disruption of the blood supply to the proximal femur. The alterations in the blood supply may occur following a traumatic event or result from a non-traumatic cause. Femoral neck fracture and hip dislocation and associated surgical procedures, corticosteroid therapy, and alcohol abuse frequently lead to AVN development. Type of fracture (displaced or undisplaced) and time between injury and surgery are the most critical factors in assessing the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 72 publications
0
75
0
2
Order By: Relevance
“…Only the study based on the Taiwanese registry diagnosis was made based on plain film, nuclear scan, or MRI. MRI is useful in the early diagnosis of AVN and can identify patients at risk of femoral head fracture [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only the study based on the Taiwanese registry diagnosis was made based on plain film, nuclear scan, or MRI. MRI is useful in the early diagnosis of AVN and can identify patients at risk of femoral head fracture [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…AVN of the jaw is a debilitating disease that occurs predominantly in people using bisphosphonates, which are medications that inhibit bone resorption [ 13 , 14 ]. The treatment of early-stage AVN primarily involves physiotherapy, whereas late-stage disease often requires surgery [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the decreased BMSCs in the ONFH femoral head, the application of BMSCs over the osteonecrotic lesion sites seems to be a reasonable revenue. Clinical trials of autologous BMSCs therapy for ONFH have shown promising results in early-stage cases [ 10 , 25 ]. However, the compromised regenerative potentials of BMSCs harvested from ONFH patients remain a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Osteonecrosis of the femoral head (ONFH), also known as avascular necrosis, is a progressive degenerative disease characterized by a disruption in blood flow to the femoral head (FH) [ 1 ]. ONFH is a multifactorial disease caused by traumatic (e.g., interruption of the ligament of teres) or non-traumatic events (e.g., chronic use of alcohol, smoking, or as a result of steroids, radiotherapy, and chemotherapy) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%